Postoperative Adrenal Insufficiency after Sellar and Parasellar Surgery: Prevalence and Result of Perioperative Glucocorticoid Replacement - แสงโพธิ์สุข, วีระวงศ์; สกุลณะมรรคา, สิรรุจน์; เทียนศรี, ธนกร (Thai Journal of Neurological Surgery, 2025)
Background: Postoperative adrenal insufficiency is an important complication after sellar and parasellar surgery. Currently, the role of perioperative glucocorticoid replacement is still unproven. Objective: To study prevalence of postoperative adrenal insufficiency and result of perioperative glucocorticoid replacement in patients with normal preoperative hypothalamic-pituitary-adrenal (HPA) axis functions undergoing sellar and parasellar surgery. Methods: A retrospective cohort study was conducted to assess postoperative adrenal insufficiency in patients who underwent sellar and parasellar surgery in Phramongkutklao Hospital between 2010 to 2016. Losgistic regression was used to analyse the correlation between postoperative adrenal insufficiency and several factors, including perioperative glucocorticoid replacement. Results: Of 79 patients, 13 patients (16.5%) were treated by transcranial surgery and 66 patients (83.5%) were treated by transsphenoidal surgery. The pathological diagnosis was non-functioning pituitary adenoma in 60.8%, growth hormone (GH)-secreting pituitary adenoma in 10.1%, prolactinoma in 2.5%, thyrotroph pituitary adenoma in 1.3%, craniopharyngioma in 5.1%, Rathkeûs cleft cyst in 7.6%, meningioma in 10.1%, and schwannoma in 2.5%. Fifteen patients (19%) had postoperative adrenal insufficiency. Perioperative glucocorticoid replacement was associated with lower rate of postoperative adrenal insufficiency, but this correlation was not statistically significant (OR = 0.63, 95%CI 0.58-9.57, p-value 0.338). In multivariate analysis, only patients with postoperative central diabetes insipidus had significantly higher rate of postoperative adrenal insufficiency (adjusted OR = 8.512, 95%CI 2.211-32.769, p-value 0.002). Furthermore, perioperative glucocorticoid replacement was not associated with any postoperative complications. Conclusion: Routine perioperative glucocorticoid replacement is not necessary in patients undergoing sellar and parasellar surgery if preoperative adrenal function is intact. In this study, we found significant correlation between postoperative central diabetes insipidus and postoperative adrenal insufficiency.